The role of physical activity, body mass index and maturity status in body-related perceptions and self-esteem of adolescents - AŞÇI, FEVZİYE HÜLYA (TAYLOR & FRANCIS LTD, 2014)
Background: Adolescence represents a transitional period which is marked by physical, social and psychological changes. Changes in body shape and physical activity especially alter and shape the psychological well-being of adolescents. Aim: The purpose of this study was to determine the role of physical activity level, body mass index and maturity status in body-related perception and self-esteem of 11-18 years old adolescents. Subjects and methods: A total of 1012 adolescents participated in this study. The Social Physique Anxiety Scale'', Body Image Satisfaction Scale'', Physical Self-Perception Profile for Children'' and Rosenberg Self-Esteem Inventory'' were administered. Physical activity level and body mass index were assessed using the Physical Activity Questionnaire'' and Bioelectrical Impedance Analyzer'', respectively. Results: Regression analysis indicated that body mass index was the only predictor of perceived body attractiveness, social physique anxiety, body image satisfaction and self-esteem for female adolescents. For male adolescents, both physical activity and body mass index were correlated with perceived body attractiveness and social physique anxiety. Pubertal status were not correlated with self-esteem and body-related perceptions for both males and females adolescents. Conclusion: In summary, body mass index and physical activity plays an important role in body-related perceptions and self-esteem of adolescents.
Keywords: Body composition; puberty; self-perceptions; SOCIAL PHYSIQUE ANXIETY; ACTIVITY LEVEL; PUBERTAL STATUS; CHILDRENS; GENDER; GIRLS; DISSATISFACTION; VALIDITY; WEIGHT; COMPETENCE